(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Radiation therapy (radiotherapy) is a type of cancer therapy in which specialists destroy cancer cells in a patient’s body by exposing them to ionizing radiation such as X-rays, gamma rays, high-energy electrons or heavy particles. It is one of the most widely used cancer treatments. Approximately half of all cancer patients require radiation therapy at some point during the course of their illness. But the use of rays, while being useful, can also be harmful.